A Computer Procedure To Simulate Progressive Rock Failure Around Coal Mine Entries - N. P. Kripakov; M. T. Melvin (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1983)
The practical application of a post-processing modeling procedure to simulate progressive rock failure around the periphery of coal mine entries is presented. This numerical scheme utilizes a simple rock model that incorporates easily obtainable input parameters consistent with basic rock mechanics principles. These parameters include the cohesion, angle of internal friction, modulus of elasticity, and Poisson's ratio of the bedded deposits that comprise the imediate roof, coal seam, and immediate floor. The geometry of the entry, along with the in situ stresses existing at a mine site prior to mining, are also considered in the analysis. The potential of this procedure as a predictive tool in determining the extent of pillar rib fracturing and yielding of the immediate roof and floor is evaluated assuming a Mohr- Coulomb failure criterion. The procedure is designed to be user oriented and is adaptable to any finite element code with linear elastic capability, making it particularly attractive to users with limited budgets and computer size.